Using spatial resource planning in geo-economics and sustainable development of the city - Mohammad Akhbari, Mohammad Akhbari (2008)
SRP (Spatial resource planning) used in the infrastructure. This type of planning is operational for management of the facility and asset of the equipments to manage devices and their integrity such as PIMS (pipeline integrity management system).the terminology of SRP is to manage from detail data of an element in the infrastructure within a data model which is as sophisticated as the real world. There are a lot of computer applications that helps engineers to manage the infrastructure like telecom, water pipe, sewerage and other urban facilities. This paper describes the way to use the SRP term for managing a city geopolitically and geo-economically.